HUBUNGAN POLA MAKAN ANAK TERHADAP TINGKAT KEJADIAN EARLY CHILDHOOD CARIES (ECC) DI KELURAHAN TANAH GARAM KOTA SOLOK - Lala Viodita; Rizanda Machmud; Hidayati Hidayati (Andalas Dental Journal, 2018)
Dental caries is the most commonly found for oral and dental diseases. It could appear in permanent and even desidual teeth. One of the oral and dental diseases prevalent to children of age 1-5 years old is termed Early Childhood Caries (ECC) which was an acute dental infection that rapidly develop from one third of primary servical maxillary incisivus into the whole teeth making white to yellowish cavity with soft caries tissue. Diet pattern gives big influence on incidence of caries. to find the relationship between children diet pattern with the case of ECC. observational analytical using cross- sectional design. Sample size was 50 children of age 2-3 years old in three different Comprehensive Treatment Post (CTP) in working area of Tanah Garam primary healthcare in Solok City. ECC prevalence in Tanah Garam District of Solok City in 2018 was 56 %. Diet pattern found mostly was cariogenic for 52 %. There was significant relationship between diet pattern with the case of ECC in Tanah Garam District of Solok City with p = 0.01. There was significant relationship between diet pattern with the case of ECC in Tanah Garam District Solok City.